Multi-scenario simulation can contribute to identify priorities for regional ecological corridors conservation - Hui Dang; Yihe Lü; Jianying Guo; Xing Wu (Ecological Indicators, 2024)
Ecological corridors, as a key component of ecological networks (EN), can strengthen linkages between ecological sources and effectively prevent further fragmentation and loss of regional habitats. Understanding the structure of ecological corridors and exploring their resilience in different scenarios can facilitate the understanding on the flows of energy and materials between ecological sources that can contribute to landscape conservation and restoration. In this study, the agro-pastoral ecotone of the North Yinshan Mountain was used as an example to conduct the landscape EN analysis with corridors as the focus. Random attack, overgrazing and urban sprawl, incremental optimization, and arterial corridors conservation scenarios were constructed. Network cascade failure simulations are introduced to explore the stability of EN under four scenarios. Among them, 12 new ecological corridors were optimized at 9 nodes, and 158 arterial corridors connected the 159 ecological sources to form the backbone of the EN. Both the arterial corridors conservation scheme and the optimization scheme of additional edges play important roles in maintaining the resilience of the EN. This provides scientific decisions for the categorization and conservation of ecological corridors to ensure the ecological integrity of functional landscapes.